2016
DOI: 10.1007/s00787-016-0832-7
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated psychotic and basic symptom characteristics in adolescents with ultra-high risk criteria for psychosis, other non-psychotic psychiatric disorders and early-onset psychosis

Abstract: While attenuated psychotic symptoms (APS) and basic symptoms (BS) are the main current predictors of psychosis in adults, studies in adolescents are scarce. Thus, we (1) described the prevalence and severity of positive, negative, disorganization, general, and basic symptoms in adolescent patients at ultra-high risk for psychosis (UHR), with other non-psychotic psychiatric disorders (PC) and with early-onset psychosis (EOP); and (2) investigated BS criteria in relation to UHR criteria. Sixty-nine 12-18-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…In our study, most PRSS reported APS at baseline, a larger proportion also presented ANS, while few showed GR plus deterioration, in line with results from other child and adolescent PRS studies (Cascio et al, 2016;Meyer et al, 2005;Spada et al, 2016;Ziermans et al, 2011).…”
Section: Prs Sample Baseline Clinical Characteristicssupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, most PRSS reported APS at baseline, a larger proportion also presented ANS, while few showed GR plus deterioration, in line with results from other child and adolescent PRS studies (Cascio et al, 2016;Meyer et al, 2005;Spada et al, 2016;Ziermans et al, 2011).…”
Section: Prs Sample Baseline Clinical Characteristicssupporting
confidence: 92%
“…Although the majority of these patients (61.5%) took medication combined with psychological intervention, a considerable number (38.5%) showed pharmacological treatment as the only intervention provided. Recent reports show similar rates of pharmacological treatment (Cascio et al, ; Ziermans et al, ). Some 65.9% of PRSS had at least one DSM‐IV‐TR diagnosis, providing an explanation for the high rates of pharmacological treatment observed.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Results have not been long in coming and we now have good evidence that many mental disorders in children and adolescents are statistically associated with soft and early signs and symptoms. Three papers are dealing with this question in this issue of ECAP [3,4,8], in areas as diverse as ADHD (attention deficit/hyperactivity disorder), psychosis or educational achievement.…”
Section: Introductionmentioning
confidence: 99%
“…This area of conflict is influenced by many different and important factors, among others, by clinicians' uncertainties about the validity of the CHR state in people with highly complex symptom combinations, mostly multiple comorbid psychiatric disorders, additional biological and environmental risk factors, and often frequent childhood adversities. In fact, several recent studies suggest that at least the psychosis CHR criteria may affect a higher proportion of adolescents than adults, with emergence of CHR criteria-based symptomatology at the same time as other mental disorders emerge, complicating the clinical picture [140][141][142]. Furthermore, in a program focusing predominantly on adolescents, younger age of onset of CHR criteria within adolescence was associated with lower conversion rates to psychosis [21].…”
mentioning
confidence: 99%